2021
DOI: 10.3390/land10080804
|View full text |Cite
|
Sign up to set email alerts
|

The Evolution of the Interactive Relationship between Urbanization and Land-Use Transition: A Case Study of the Yangtze River Delta

Abstract: In recent years, the impact of land-use systems on global climate change has become increasingly significant, and land-use change has become a hot issue of concern to academics, both within China and abroad. Urbanization, as an important socioeconomic factor, plays a vital role in promoting land-use transition, which also shows a significant spatial dependence on urbanization. This paper constructs a theoretical framework for the interaction relationship between urbanization and land-use transition, taking the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(9 citation statements)
references
References 33 publications
(40 reference statements)
0
7
0
Order By: Relevance
“…Although the HAI in the Yangtze River Delta in 2018 was slightly lower than that of the Beijing-Tianjin-Hebei region, its growth trend in the Yangtze River Delta was steeper. Evidence has shown that in the Yangtze River Delta, rapid urbanization intensifies the trend toward land fragmentation and promotes the rapid expansion of construction land [45].…”
Section: Implications Of Human Activity Intensitymentioning
confidence: 99%
“…Although the HAI in the Yangtze River Delta in 2018 was slightly lower than that of the Beijing-Tianjin-Hebei region, its growth trend in the Yangtze River Delta was steeper. Evidence has shown that in the Yangtze River Delta, rapid urbanization intensifies the trend toward land fragmentation and promotes the rapid expansion of construction land [45].…”
Section: Implications Of Human Activity Intensitymentioning
confidence: 99%
“…This study referred to the research results of Niu et al [62], Deng et al [10], and Han et al [63] to analyze the intrinsic mechanism of the effect of the N-TU on the ULUE in four paths: social urbanization, economic urbanization, demographic urbanization, and spatial urbanization (Figure 2). H2.…”
Section: Impact Mechanismmentioning
confidence: 99%
“…However, most of the topics discussed are tourism development and impacts [19,[22][23][24][25], freshwater intake sources and strategies [41], water quality and monitoring [42], carbon emissions [43], hydrology [44], water pollution [45], and marine and freshwater ecosystems [46]. In addition, the current research topics focusing on the Yangtze River only focus on air pollution [47], water pollution [48], energy utilization rate [49], urban land development and utilization rate [50], cruise tourism development [51], and residents' environmental literacy and decision-making participation [52]. Most of them are simply discussed from a single perspective, such as that of residents and tourists [51][52][53], but there is no hybrid research method, and most are based on the perspective of consumer willingness to buy property, revisit, or the two perspectives combined to discuss together.…”
Section: Introductionmentioning
confidence: 99%